PELATIHAN DAN PENDAMPINGAN PARIWISATA BERBASIS LINGKUNGAN DAN PARTISIPASI MASYARAKAT DALAM MENGEMBANGKAN EKOSISTEM LAUT (DESA EDUWISATA) - Subhan Widiansyah; Nurul Hayat; Stevany Afrizal (MULIA (Jurnal Pengabdian kepada Masyarakat), 2023)
Community Service through the "Edutourism Village" is an implementation of the third tridharma of higher education, namely Community Service, as well as to equip lecturers and students of the FKIP Untirta Sociology Education Study Program on how to carry out service that produces work products with the community, and accompanied by professional instructors as partners. The purpose of carrying out this service is apart from developing tourism in the Ujung Kulon area, this is also done together with the community so that they can maintain and preserve the marine ecosystem in the Ujung Kulon area as a result of the Tsunami that occurred at the end of 2018. The implementation method used in community service activities This is providing information and skills through lecture methods and material presentations as well as group discussions. Then proceed with simulation.